A Hepatitis B virus, hepatitis C virus and human immunodeficiency virus infection in Expatriate workers and Libyan people in Darna: Hepatitis B virus, hepatitis C virus and human immunodeficiency virus infection in Expatriate workers and Libyan people in Darna - Hamza Khalifa Ibrahim; Noor alhooda. M. Alawkally; Mareei. Al douakali Ali; Alreda Miloud Al Al-awkally; Nesrine Miloud Al-awkally; Aejeeliyah Yousuf (Brilliance: Research of Artificial Intelligence, 2022)
Viral hepatitis constitutes a global health problem; previous studies have affirmed a considerable morbidity and mortality from both acute infections and chronic complications. On the other hand, Human Immunodeficiency Virus (HIV) infection is also of known burden. Determining prevalence measures of these viruses is crucial for establishing appropriate country specific strategies regarding prevention, diagnosis, and containment. The data for this research were records from 2-year period from 20-2018, a total of 1.968 cases were collected from two years. In 2017, a total of 696, (429) Libyan and (267) expatriate, only one infected Libyan and expatriate equally with HCV in June. A total of 1272 cases in 2018, 543 were no Libyan cases with viral infection and 729 Expatriates recorded infection with 8 cases (3 HBSAg and 5 HCV) in November, 7 (one cases with HIV, two cases with HBSAg and 4 cases with HCV). According to the seasons, HIV was recorded with one case (10) in the autumn while the highest HBSAg infected was observed in autumn 5 (50%) followed by summer 4 (40%) and the highest HCV infected was recorded in autumn 9 (90%) followed by summer 3 (30%) and winter 1 (10%).